(untitled) (Jurnal Bahasa, 2006)
Language mixing is obviously a universal phenomenon, especially for languages that experience intercultural interaction. The terms such as pidgin, creole, code switching and code mixing represent the concept of that phenomenon. In Malaysia, as early as 1934, Za `ba had dis-cussed it in his well-known work Ilmu Mengarang Melayu. This artitle, on one hand discusses mixed language as a sociolinguistics re-ality that becomes one of the elements which illustrate the Malaysian linguistic scenery. On the other hand, this article discusses the impact of it to the language planning which has its significance in nation-building process. The main issue that needs to be discussed is how mixed language ought to be accepted as a sociolinguistics reality and at the same time language planning as a means of nation-building is not affected by the uncontrolled usage of it, especially in the official and intellectual domains.